2020
DOI: 10.5713/ajas.19.0980
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intermittent feeding and cold water on performance and carcass traits of broilers reared under daily heat stress

Abstract: The effect of intermittent feeding and cold water on performance and carcass traits of broilers reared under daily heat stress ABSTRACT Objective: This study aimed to determine the effect of intermittent feeding and cold water on performance and carcass traits in broiler chickens between 4 to 6 wk of age with daily high temperature. Methods: Broilers were assigned to four treatment groups according to a 2x2 factorial design between 22 to 42 d of age (80 broilers per treatment, 4 replications). Broilers were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…In the previous study we conducted on the same chicken materials (Erensoy et al, 2020a), it is known that IF and CW does not affect water consumption, so we speculated that the difference in water consumption does not cause the deterioration in the litter quality. However, chickens consuming CW showed more panting behavior at 4, 5, and 6 weeks of age (see Fig.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the previous study we conducted on the same chicken materials (Erensoy et al, 2020a), it is known that IF and CW does not affect water consumption, so we speculated that the difference in water consumption does not cause the deterioration in the litter quality. However, chickens consuming CW showed more panting behavior at 4, 5, and 6 weeks of age (see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The accompanying heat stress to excessive live weight makes it challenging to manage in modern broilers, which are already vulnerable in many aspects such as physiological, welfare and health. In our previous study (Erensoy et al, 2020a) had already demonstrated the effects of feeding type and water temperature on performance and carcass traits. We hypothesized that these management tools could also improve some welfare and meat quality traits under heat stress conditions.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Body defects include footpad dermatitis (FPD), hock burn (HB), and the breast burn-redness (BB) level of 150 animals (75 male and 75 female) randomly from each group. FPD, HB, and BB levels were determined using a visual scoring system between 0-3 scale (Erensoy et al 2020b;de Jong et al 2014;Welfare Quality 2009). Litter moisture content was determined after the chickens were slaughtered.…”
Section: Data Collectionmentioning
confidence: 99%